Thermophysical Properties of Zirconia Toughened Alumina Ceramics with Boron Nitride Nanotubes Addition. Issue 15 (7th September 2020) - Heon Kim, Chi; Go, Eun Byul; Tae Kim, Hyo
Abstract: The demand for high thermal conductivity substrates with electrically insulating materials are increasing with the emerging markets in power electronics and mobile telecommunication device packages. Effective heat transfer in those packages is important to provide high performance and reliability of the product. This paper mainly presents the thermophysical properties of zirconia toughened alumina ceramics with the addition of small amount of boron nitride nanotubes (BNNTs). The effects of the boron nanotubes addition on the sintering behavior, the microstructure and the thermal properties of the yttria-stabilized zirconia toughened alumina (YZTA), nanocomposite ceramics are investigated. The addition of 0.3 wt% boron nitride nanotubes into the YZTA matrix enhanced the thermal diffusivity as well as a mechanical strength. Above all, the addition of boron nitride nanotubes greatly decreased the coefficient of thermal expansion (CTE) of the composites in which the CTE of pure alumina increases with increasing temperatures. Moreover, the BNNTs added YZTA composites revealed a drastic decrease in CTE at high temperature range, 400–800 °C. This enhanced thermal stability of YZTA–BNNT composites may have a potential application to the high temperature structural ceramics and high power semiconductor packaging substrate.